The effect of environmental performance and green accounting on financial performance with corporate social responsibility as a mediating variable - Amelia, Annisa Noor; Irawan, Ferry (Educoretax, 2025)
This research aims to determine the effect of environmental performance and green accounting on financial performance with corporate social responsibility as a mediating variable. The population in this study were energy and basic material sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The sample was selected using purposive sampling, with the result 91 unbalanced data from 29 companies. Data were obtained from sustainability reports, annual reports, and financial statements accessed through the IDX or company websites. Hypothesis testing in this study using panel data regression analysis with STATA V.17, including descriptive statistical tests, model selection, classical assumption tests, coefficient determination, partial tests, and Sobel test. The results of this research show that environmental performance and green accounting have positive effects on corporate social responsibility. Meanwhile, environmental performance and green accounting have no effect on financial performance, whereas corporate social responsibility has a negative effect on financial performance. However, corporate social responsibility cannot mediate the relationship between environmental performance and green accounting on financial performance.